2003
DOI: 10.1023/a:1022899207206
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatic stress effects of working with survivors of criminal victimization

Abstract: This paper focuses on the consequences for providers of working with survivors of traumatic events, particularly criminal victimization. The paper reviews the relevant research and treatment literature associated with secondary traumatic stress (STS) and related variables (burnout, compassion fatigue, vicarious trauma, and countertransference). The latter part of the paper identifies the most important mitigating factors in the development of STS. These include good training specific to trauma work, a personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
247
1
15

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(283 citation statements)
references
References 23 publications
11
247
1
15
Order By: Relevance
“…Figley (2002b) has suggested, however, that secondary trauma is not the same as burnout syndrome and that each should be treated as having a unique effect on a professional's well-being (see also Jenkins & Baird, 2002;Sabin-Farrell & Turpin, 2003;Salston & Figley, 2003). Burnout syndrome is often defined as a response to prolonged exposure to demanding interpersonal situations and is characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment (Maslach, Schaufeli, & Leiter, 2001).…”
Section: Compassion Fatigue (Cf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Figley (2002b) has suggested, however, that secondary trauma is not the same as burnout syndrome and that each should be treated as having a unique effect on a professional's well-being (see also Jenkins & Baird, 2002;Sabin-Farrell & Turpin, 2003;Salston & Figley, 2003). Burnout syndrome is often defined as a response to prolonged exposure to demanding interpersonal situations and is characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment (Maslach, Schaufeli, & Leiter, 2001).…”
Section: Compassion Fatigue (Cf)mentioning
confidence: 99%
“…For example, a history of trauma, lower social support, and an inability to cope with the demands of caregiving are thought to increase the likelihood of developing CF. Previous research has tended to support the hypothesized relationships between these risk factors, CF, and psychological distress (Figley, 1995(Figley, , 2002aNelson-Gardell & Harris, 2003;Sabin-Farrell & Turpin, 2003;Salston & Figley, 2003;Schauben & Frazier, 1995). Schauben and Frazier (1995), for example, found that female psychologists and violence counselors with a higher percentage of sexual violence victims as clients reported more vicarious trauma and that this was related to greater psychological problems.…”
Section: Compassion Fatigue (Cf)mentioning
confidence: 99%
See 1 more Smart Citation
“…In regards to forensic interviewing specifically, the participants reported a mean of 5.5 years of experience, with a range of 0.5 to 18 years. All of the participants reported that they had experienced vicarious trauma symptoms, which were indicated by physical symptoms, emotional symptoms, behavioral symptoms, work related issues, interpersonal problems, and/or professional efficacy such as a decrease in concern and esteem for clients (Baird & Jenkins, 2003) [11,[24][25][26][27][28]; Perry, 2003; [29]. Researchers did not inquire about historical mental health and/or trauma of participants prior to the commencement of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Employees may lack the experience of satisfaction when there is closure to an interaction because their clients face ongoing, complex, and emotionally laden issues (Guy et al, 2008). Due to this high-stress environment, many researchers, including Salston and Figley (2003), have pointed to compassion fatigue as a constant risk of working in an emotionally intense job. Emotional labor can result in increased absenteeism, increased use of health benefits, poor performance, high turnover rates, more workers' compensation claims, lower morale, and increased substance abuse or misuse (Jacobson, Paul, and Blum, 2005).…”
Section: Negative Impacts Of Emotionally Intense Jobsmentioning
confidence: 99%